Supramolecular colloidal motors via chemical self-assembly. (December 2022) - Zhang, Qihan; Yan, Yuwei; Liu, Jun; Wu, Yingjie; He, Qiang
Abstract: A colloidal motor can convert energy stored in the environment to achieve mechanical motion and exhibit dynamic behaviors in fluids. To overcome the challenges presented to a colloidal motor, controlled molecular self-assembly technology provides new opportunities for the precise fabrication of various nanoarchitectures and facilitates fundamental research on rational design, multifunctionalization, propulsion, and controlled movement of colloidal motors. These molecular assembled colloidal motors, also called supramolecular colloidal motors, can perform special tasks at the micro- and nanoscale in the fields of biomedicine, nanotechnology, and environmental remediation. In this feature article, we first introduce the recent progress of controllable self-assembly of spatially asymmetric supramolecular colloidal motors with variable sizes, structures, and functions and discuss the relationship between structure and propulsion. Next, we review the research progress of this type of colloidal motors in biomedical and environmental fields. Finally, we propose the challenges of the supramolecular colloidal motors and future development direction. Graphical abstract: Image 1 Highlights: Rational design and controlled molecular self-assembly of supramolecularly colloidal motors are summarized. The structure–propulsion relationship of chemically self-assembled colloidal motors is discussed. The potential application of colloidal motors in biomedical and environmental fields is outlined. Perspectives on the challenges and future direction of colloidal motors are given.